Self-fulfillment and Work in the Light of "The Acting Person" of Karol Wojtyla - Peralta, Jose Francisco, Jr. (Divine Word International Journal of Management and Humanities (DWIJMH) (ISSN: 2980-4817), 2024)
This study focused on the philosophy of Karol Wojtyla in his book entitled “The Acting Person” about one of the activities of a human person, i.e. work itself. Although he did not dedicate any topic to human work, his very explanation of the action of the person as both subjective and personal is what human work is. Work, as lived experience, is one of the many actions a human person is capable of doing. On one side, despite the toilsome or burdensome character of human work, there exists a uniqueness in the person apart from beings. On the other, despite the uniqueness and value of work, there still exists a dehumanization from work, that of being replaced by faster and seemingly more reliable machinery or technology. However, work, as one of the many voluntary human actions, actually reveals the person and goes beyond his cosmological situatedness as simply a man. It is in the transcendence in action that changes these negative connotations of work putting the person as the subject and never the object of work. Work is a true manifestation of, first and foremost, our consciousness. The human person is not only conscious of his actions but even conscious of his conscious acting. Since the person is conscious of what he is doing, he is the efficient cause, that is, the active agent that brings about a series of effects. This conscious and efficacious acting brings about what Wojtyla would call self-determination, self-possession and self-governance. Lastly, work as one of the conscious and efficacious actions of a human person brings about self-fulfilment or in other words “felicity,” knowing that it is the same person who creates and contributes, in and through his work how and what it is to be human.